(untitled) - Waite, Mitchell (Carmel, Ind., USA, 1990)
The most complete introduction to UNIX! As UNIX becomes the premier operating system for multiuser and multitasking environments, this text is becoming one of the leading references. Includes Version 4.3 BSD (Berkeley Standard Distribution). Presents the vi and ex editors. Covers the C shell and file management commands.
Keywords: UNIX (Computer file),UNIX (Tệp máy tính)